Improving Learning Engagement and Performance through Google Sites-Based Project Learning in Vocational Network Education - Wici Aan Savitri (Jurnal Vokasi Teknik Informatika, 2025)
The advancement of web-based technology has opened new opportunities for enhancing the quality of teaching and learning in vocational education. This study aims to examine the effectiveness of Google Sites as a digital learning media combined with the Project-Based Learning (PjBL) model in improving student learning outcomes in the subject of Network System Administration. Conducted using Classroom Action Research (CAR) in two cycles, this study involved 31 students from class XI TKJ at SMKN 5 Padang. Data were collected through observation, documentation, and learning achievement tests. The findings show a consistent increase in students’ learning engagement and performance. The average learning outcomes rose from 67.42 (pre-cycle) to 78.86 (cycle II), with student mastery increasing from 68% to 90%. The integration of Google Sites facilitated independent and flexible access to learning materials, while the PjBL model encouraged collaborative problem-solving and practical skill development. These results suggest that the combination of interactive digital media and project-based instruction significantly enhances the effectiveness of vocational learning environments.